Analisis Bimbingan Kelompok Berbasis Daring dengan Teknik Discussion Group dalam Meningkatkan Minat Belajar Siswa - Mahmuddah Dewi Edmawati; Sri Rahayu Purwaningsih; Fatimah Fitriana; Dandy Satria Fauzan (Institut Agama Islam Neegri Madura, 2021)
Abstract. The effect of the Covid (Coronavirus) has constrained a few neighborhood governments to settle on the execution of strategies to close understudy exercises at school and carry out internet learning frameworks or distance learning. The approach for executing internet learning has been in actuality since Walk 2020 in all schools in Indonesia, including SMAN 1 Nguter. One of the impacts of learning with this online framework is the decrease in understudy revenue in SMA N 1 Nguter. This examination is a library research, which is a kind of exploration that is utilized to gather top to bottom data and information through different written works and pertinent past research results to acquire answers and hypothetical establishments in regards to the issues to be contemplated. This examination intends to look at the job of online-based gathering direction with bunch conversation methods in expanding understudy revenue in learning. Gathering direction with bunch conversation procedures can expand learning inspiration, this is on the grounds that in bunch direction there is a gathering dynamic that can make expanded understudy learning inspiration. Through bunch direction exercises, all gathering individuals lead conversations, give and get data, foster correspondence and relational abilities, inspire each other so that bunch individuals' learning inspiration increments. The execution of online-based gathering direction is one successful methodology because of the pandemic that doesn't permit the execution of up close and personal direction and advising exercises. Keyword : Group Guidance; E- Learning; Interest in Learning